Vertical bearing capacity of spun precast concrete piles in liquefiable soil: a case study - Farzana, Kh Afia; Ahmed, Khondaker Sakil; Ahmed, Mohiuddin; Ansary, Mehedi Ahmed; Abedin, Md Zoynul (Geotechnical research, 2024)
Spun precast prestressed concrete (SPC) piles have been used in many parts of the world as a viable foundation alternative. This study assessed the load-carrying capacity of SPC piles passing through a deep soft subsoil layer and resting on a dense sand layer. The vertical bearing capacity of an SPC pile was estimated using various analytical methods and static pile load tests for the Jolshiri area of Dhaka, Bangladesh. The liquefaction potential of the site was assessed using local seismic site conditions and field and laboratory test data. The liquefaction analysis suggested that the topsoil layer was liquefiable to a depth of 4.5 m. The capacity obtained from the load test was compared with those obtained from different methods, the ultimate push-in load and local design guidelines. Finite-element analysied (FEA) was performed considering the hardening soil model using the Plaxis 3D software to simulate field conditions. The load–settlement response obtained from FEA showed good agreement with the test results. The capacity examinations primarily suggested that SPC piles could be a viable foundation solution for the subsoil conditions of the Jolshiri Abashon area of Dhaka.